2016
DOI: 10.7567/jjap.55.04es14
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of the potential-induced degradation of photovoltaic modules fabricated using flat mono-crystalline silicon cells with different surface orientations

Abstract: This paper deals with the dependence of the potential-induced degradation (PID) of flat, p-type mono-crystalline silicon solar cell modules on the surface orientation of solar cells. The investigated modules were fabricated from p-type mono-crystalline silicon cells with a (100) or (111) surface orientation using a module laminator. PID tests were performed by applying a voltage of −1000 V to shorted module interconnector ribbons with respect to an Al plate placed on the cover glass of the modules at 85 °C. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Since then, a lot of work has been done to develop PID-free modules. All related proposals have the attempt to increase the resistance of the LC pathways in common, which can be done at the cell level by selecting the appropriate crystal orientation [29], ARC coating [14], [30], [31] or passivation layer [32], [33]; at the module level, manufacturers normally use high resistive encapsulations [34]- [38] or alminosilicate and chemically tempered glass [39]. Along similar lines, the stress test of the PV modules to detect the propensity for PID formation has been carried out since 2010 [2], [14], [40]- [43] based on different combinations of voltage, temperature and way of reducing the front glass conductivity: humidity or conductive foils.…”
Section: Pid Testing and Standardsmentioning
confidence: 99%
“…Since then, a lot of work has been done to develop PID-free modules. All related proposals have the attempt to increase the resistance of the LC pathways in common, which can be done at the cell level by selecting the appropriate crystal orientation [29], ARC coating [14], [30], [31] or passivation layer [32], [33]; at the module level, manufacturers normally use high resistive encapsulations [34]- [38] or alminosilicate and chemically tempered glass [39]. Along similar lines, the stress test of the PV modules to detect the propensity for PID formation has been carried out since 2010 [2], [14], [40]- [43] based on different combinations of voltage, temperature and way of reducing the front glass conductivity: humidity or conductive foils.…”
Section: Pid Testing and Standardsmentioning
confidence: 99%
“…Recently, potential-induced degradation (PID) has been identified as a central reliability issue of photovoltaic (PV) cell modules. Causing marked degradation in a short time, such as several months, PID is triggered by potential differences between grounded frames and the active circuit of cells in modules in the field. The PID behavior varies to a considerable degree depending on PV cell material, structure, and PID-stress intensity. , For instance, sodium-penetration-type PID (including shunting-type PID), polarization-type PID, and corrosion-type PID , are known to occur depending on these factors.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of results from experimentation is probably attributable to the fact that apparent polarization-type PID does not occur in front-emitter p-type c-Si cells. This lack of occurrence might be partly attributable to the fact that polarization-type PID in front-emitter p-type c-Si cells occurs under opposite bias to that causing shunting-type PID, which has been studied most actively. Jonai et al have briefly reported that polarization-type PID occurs under a positive bias in p-type Al-BSF cells with SiN x /SiO 2 stacked passivation layers and that SiO 2 layers underneath SiN x layers play an important role in the occurrence of polarization-type PID.…”
Section: Introductionmentioning
confidence: 99%
“…The application of PV cells in large‐scale PV systems requires that one understand the behaviors and mechanisms of their potential‐induced degradation (PID). [ 8–14 ] This PID of PV modules frequently occurs in large‐scale PV systems. Conventional PV modules are generally composed of soda‐lime silicate glass as cover glass, ethylene–vinyl acetate (EVA) copolymer as an encapsulant, a backsheet, and an aluminum (Al) frame.…”
Section: Introductionmentioning
confidence: 99%
“…Although the first report of PID in c‐Si PV modules is that, in n‐type interdigitated back‐contact (IBC) c‐Si PV modules, [ 15 ] many researchers have specifically examined PID in conventional p‐type c‐Si modules for practical reasons since around 2010. [ 9–14 ] Efforts of researchers in the field have contributed to remarkable progress in elucidating PID and related phenomena affecting conventional p‐type c‐Si PV modules; a brief review is presented in Section 2. Understanding PID in p‐type c‐Si PV modules will help clarify many aspects of PID in n‐type c‐Si PV modules.…”
Section: Introductionmentioning
confidence: 99%